Synoptic and Dynamic Analysis of Heavy Rainfall Events in the Southern Coastal Caspian Sea In Comparison With Iran Case Study (1381/9/15-1381/9/20) - Hamid Noori; Alireza Yildroomi (نشریه جغرافیا و برنامه‌ریزی, 2012)
This research, one of the most covering rainfall times (from1381/8/6 to 1381/10/5) in Iran study and then synoptic and dynamic analysis of it's the heaviest rainfall cluster (from 1381/9/15 to 1381/9/20) explain using environmental to circulation pattern method. In this time more than 60% of Iran stations experienced rainfall and also, the number of heavy rainfall events were recorded in the southern coastal Caspian see. After drawing of Isorain maps in studied days, rain maximum points and its gravity centers calculated. Then, pressure surface patterns, geopotential, humidity advection, front, jet stream and Q-vector maps were drawn in different levels. Analysis of pressure of see level maps showed that pressure gradient reinforcement between Black see high pressure and Mediterranean low pressure and between Black see high pressure and the eastern north of Caspian sea  low pressure are effective to produce these heavy rainfalls in west, southern west of Iran and the southern coastal Caspian sea. Maps geopotential showed that there are two main patterns in this studied time, as role of the eastern north of Caspian Sea trough (part of long through of Mediterranean) is very important. Analysis of humidity advection maps showed that Mediterranean sea and Red sea in upper levels and Persian Golf and Oman sea in lower levels are sources of humidity for heavy rainfalls, as them role in different days aren’t alike. However, heavy rainfall events in the southern coastal Caspian sea were provided via Mediterranean sea in 500(ha) level, Mediterranean sea and Red sea in 600 and 700 (ha) levels and all of main sources of humidity (Black sea, Mediterranean sea, Persian Golf, Red sea and Caspian sea). Polar front, north of Red sea-north of Persian Golf front and composition of subtropical jet stream and polar front jet steam in the east of Iraq can be from reasons of producing and strengthening of vertical movements. Also, analysis of Q-vector maps with point of convergence regions shows the important role Caspian sea, Mediterranean sea, Black sea, Persian Golf and Oman sea to producing of raising movements in different levels and times and its follow to forming of heavy rainfall events in the southern coastal Caspian sea and Iran.